Stylistica of Maulid Simtud Durar's Repetition Created by Habib Ali Bin Muhammad Husein Al-Habsyi - Huda, Nur; Sa'dudin, Ihsan (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to describe the repetition and its effects in